Hematological Parameters as Indicators for Litter size and Pregnancy Stage in Awassi ‎Ewes - M Khazaal, Neam; F Alghetaa, Hasan; Baqur S Al-Shuhaib, Mohammed (The Iraqi Journal of Veterinary Medicine, 2023)
Physiological status and litter size can indeed have a significant impact on ewes’ ‎hematological parameters, which are essential indicators of their health. Therefore, this study ‎examined the hematological profiles of ewes during pregnancy with single and twins in the ‎Awassi ewes. The present study involved 232 ewes in good health and at sexual maturity. ‎Among them, 123 ewes had single pregnancies, while 109 ewes had twin pregnancies. The age ‎range of the ewes included in the study was between 3.5 and 4.5 years. Hematological tests ‎were conducted on the sheep’s blood samples promptly following collection. The findings ‎demonstrated variations in hematological parameters among pregnant ewes, with differences ‎based on litter size. Ewes carrying twin pregnancies exhibited significantly higher levels of ‎red blood corpuscular, hemoglobin, packed cell volume, and mean corpuscular hemoglobin ‎concentration during pregnancy. In comparison to single-pregnant ewes, Awassi ewes with ‎twin pregnancies displayed elevated counts of white blood cells, lymphocytes, granulocytes, ‎and granulocyte percentage compared to ewes with single pregnancies. Awassi ewes with twin ‎pregnancies also exhibited a strong positive correlation with the leukocytes and erythrocytes ‎constituents. In conclusion, these findings indicate that litter size significantly influences ‎hematological parameters, highlighting the importance of considering the physiological status ‎and litter size as indicators of ewes’ health. The findings have practical implications in sheep ‎breeding and reproduction, as they can be utilized to enhance the diagnosis, prognosis, and ‎treatment of related conditions‎.